The Pronunciation of English Fricatives in the Speech by a Non Native Speaker - Titah Madriyanthi Utama, Luh Gde (Humanis; Vol 22 No 2 (2018), 2018)
The title of this study is “The Pronunciation of English Fricatives in the Speech by a Non Native Speaker”. The topic was chosen based on the fact that most of the non-English speaking people are having difficulties with the pronunciation of the fricatives. Moreover, this study was also taking the unique characteristic of Balinese people in pronouncing the English fricative sounds which are delivered in a speech by the governor of Bali, I Made Mangku Pastika. There were two videos of his speech used in this study, the first was a formal speech from the speech of the tenth commemoration of Bali bombing tragedy, and the second speech was a non-formal speech at his interview event. This study identified the words with fricative sounds and their pronunciations according to Standard English, identified how the words are pronounced by the speaker, and identified problems that occurred in the pronunciation through spectrograms. The data were analyzed by using qualitative method with descriptive analysis technique. This study found various words with fricative sounds in both formal and non-formal speech. There were also some differentiations in the pronunciation of fricatives by the speaker, compared with in Standard English. The spectrogram analysis of the pronunciation found the exaggeration of the speaker in pronouncing the fricatives, both in his formal and non-formal speech.